HUBUNGAN DUKUNGAN KELUARGA DENGAN KEPATUHAN MINUM OBAT PASIEN HIPERTENSI LANSIA DI WILAYAH KERJA PUSKESMAS SUNGAI CUKA KABUPATEN TANAH LAUT - Yugo Susanto (Jurnal Ilmiah Manuntung, 2015)
One of communicable diseases become very serious health problem was hypertension. The purpose of hypertension therapy was to control blood pressure in range of normal blood pressure, it is needed the adherence for hypertension therapy. The family supportcould improved healthy status. Patient with family support  feel that people care, so it could directed patient to improve their healthy lifestyle.The purpose of this study was to determine elderly family support, medication adherence in elderly hypertensive patients, and analyzedthe correlation between the family support with the adherence ension in elderly hypertension patients in Puskesmas Sungai Cuka Tanah Laut.This study was conducted with the cross sectional design in December 2014 until January 2015. Population was280the elderly patient in the region of  primary public health Sungai Cuka and 164 of them were used for sample. Data was collected by completion questionnaires family support and Morisky Modification Adherence Scale (MMAS)questionnaires. Data analysis was performed by gamma test with 95% confidence level.Based on the results, that Elderly who have family support by category 23.8% lower category, middle category were 64%, high category were 11.6%, and 0.6% were very high category. The adherence degree of elderly hypertension patientwere 45,7% low adherence degree, moderate adherence degreewere 36%, and high adherence degree were 18.3%. There were a correlation between the family support andthe medication adherence in elderly hypertension patients at Puskesmas Sungai Cuka Tanah Laut. (γ =0.295).